Wychowanie księcia Henryka Lubomirskiego na tle idei epoki oświecenia - Polak, Szymon Mikołaj (Biuletyn Historii Wychowania, 2023)
The concept of upbringing was truly revolutionised in the 18th century. From the theses of the English scholar John Locke, who encouraged changes to the approach to young people and educating their spirit (mind) so that they would become righteous and just citizens, to the ideas introduced by the Geneva-based philosopher Jean Jacques Rousseau, suggesting that a child is a being completely different from an adult, so the concept of education should also be completely different. In Poland, there were some reflections of the aforementioned changes in education and upbringing, as evidenced by Prince Henryk Lubomirski, who at a very young age was placed under the care of his relative, Princess Izabela Lubomirska, née Czartoryska. It was she, influenced primarily by Jean Jacques Rousseau, who decided to raise Prince Henry according to the standards of the time.